The relationship between contact to cat and the development of asthma in children - Made lndah Nastiti Utami Budha; Roni Naning; Ketut Dewi Kumara Wati (Indonesian Pediatric Society, 2009)
Background Data suggesting history of direct or indirect contactto cats are either protective, has no effect or increase risk ofsensitization and asthma development.Objective To determine the relationship between childhoodcontact to cat and the development of asthma in children.Methods A case control study was conducted in Denpasar sinceDecember 2006 until Juli 2008. In this study, subjects withasthma (cases group) were selected for comparisons to a series of healthy subjects without asthma (controls group). Forty-sevensubjects (3-12 years) with asthma were recruited and matched(age and sex) with 4 7 healthy and non asthma controls. Data were collected using two kinds of questionnaires, i.e: ISAAC, ATS 78, and Robertson modification questionnaire from Medical School, University of Indonesia, which had been validated to determine asthma and asthma risk factors questionnaire. Data were analyzed as univariate by using chi-square or Fisher's exact test, and multivariate analysis by stepwise logistic regression model.Results Result of univariate analysis showed that there were seven significant risk factors of asthma. Using multivariate analysis, contact to cat was significant risk factor for asthma [OR: 4.5 (95% CI 1.3 to 16.0), P= 0.020]. Other significant risk factors were; contact to cockroach [OR: 11.7 (95% CI 2.6 to 51.6), P= 0.001], use of kapok mattress [OR: 6.4 (95% CI 1.4 to 29.0), P= 0.015], passive smoker [OR: 4.7 (95% CI 1.3 to 17.0), P= 0.018], and atopic history [OR: 9.2 (95% CI 2.3 to 36.7), P= 0.002].Conclusions There was a relationship between childhood contactto cat and the development of asthma in children. Risk factors that statistically significant were; contact to cockroach, use of kapok mattress, passive smoker, and history of allergy in study subject.